Laminated film for projection display, laminated glass for projection display, and projection display system

By designing a high-thickness heat sealing layer and a structure containing silica particles in the laminated film for projection image display, the problems of insufficient impact resistance and image display quality of laminated glass in the prior art are solved, and efficient image display and good physical performance are achieved.

CN120112834APending Publication Date: 2025-06-06FUJIFILM CORP
View PDF 29 Cites 0 Cited by

Patent Information

Application Number
CN202380075022.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-17
Filing Date
2023-11-15
Publication Date
2025-06-06

AI Technical Summary

Technical Problem

The laminated glass with a laminated film for projection image display cannot simultaneously have high impact resistance and excellent image visual recognition.

Method used

By designing a laminated film for projection image display including a support, a selective reflective layer and a heat sealing layer, the average thickness of the heat sealing layer is more than 5 μm, the surface roughness is within a predetermined range, and silica particles are contained, so that the impact resistance and image display quality of laminated glass are improved.

Benefits of technology

It achieves high impact resistance and excellent image visual recognition of laminated glass, and is suitable for automotive and other application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120112834A_ABST
    Figure CN120112834A_ABST
Patent Text Reader

Abstract

Provided are: a laminated film for displaying a projection image, which has excellent impact resistance and excellent visibility of an image projected onto a laminated glass for displaying a projection image when the laminated glass for displaying a projection image is formed by sandwiching two glass substrates; provided are laminated glass for projection display and a projection display system. This laminated film for displaying a projected image has a support, a selective reflection layer disposed on one surface side of the support, and a heat-sealing layer disposed on the other surface side of the support, the average thickness of the heat-sealing layer being 5 [mu] m or more, and the surface of the heat-sealing layer on the opposite side from the support side exhibiting predetermined characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated film for projection image display, a laminated glass for projection image display and a projection image display system. Background Art

[0002] By embedding a half mirror film (reflective film) in a laminated glass used for a windshield of an automobile or the like, the half mirror film (laminated glass) can be used for a projection image display system such as a head-up display system.

[0003] Patent Document 1 discloses a projection image display laminated film suitable for use in a projection image display device. The projection image display laminated film is sandwiched between two glass substrates and used as a projection image display laminated glass.

[0004] Previous technical literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2020 / 179787 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] On the other hand, there is a demand for further improved performance of laminated glass for projection image display obtained by using the above-mentioned laminated film for projection image display.

[0009] For example, in view of application to automobiles, laminated glass for projected image display is required to have excellent impact resistance.

[0010] Furthermore, it is required that the laminated glass for projected image display can project a projection image without distortion.

[0011] As a result of studying the laminated film for projection image display described in Patent Document 1, the present inventors have found that the laminated glass for projection image display including the laminated film for projection image display cannot achieve the above-mentioned properties and needs further improvement.

[0012] The present invention aims to provide a laminated film for projection image display which has excellent impact resistance when sandwiched between two glass substrates and has excellent visibility of an image projected on the laminated glass for projection image display.

[0013] Furthermore, another object of the present invention is to provide a laminated glass for projection image display and a projection image display system.

[0014] Means for solving technical problems

[0015] The present inventors have found that the above-mentioned problems can be solved by the following structure.

[0016] (1) A laminated film for projected image display, comprising:

[0017] Support body;

[0018] A selective reflection layer disposed on one surface side of the support: and

[0019] A heat seal layer is disposed on the other surface side of the support,

[0020] The average thickness of the heat seal layer is more than 5 μm.

[0021] The arithmetic mean height Sa in a field of view of 3700 μm in length and 4900 μm in width was measured at three different locations on the surface of the heat seal layer opposite to the support side, and the average value A of the arithmetic mean height Sa of each location was 40 nm or less.

[0022] The arithmetic mean height Sa in a field of view of 180 μm in length and 240 μm in width was measured at three different locations on the surface of the heat seal layer opposite to the support side, and the average value B of the arithmetic mean height Sa at each location was 7 nm or more.

[0023] (2) The laminated film for projection image display according to (1), wherein

[0024] The water contact angle of the surface of the heat seal layer on the side opposite to the support side is 90° or less.

[0025] (3) The laminated film for projection image display according to (1) or (2), wherein

[0026] The heat seal layer comprises polyvinyl acetal resin.

[0027] (4) The projection image display laminated film according to any one of (1) to (3), wherein

[0028] The heat seal layer contains silica particles,

[0029] The content of the silica particles is 1% by mass or more based on the total mass of the heat seal layer.

[0030] (5) The laminated film for projection image display according to (4), wherein

[0031] The content of the silica particles is 7% by mass or more based on the total mass of the heat seal layer.

[0032] (6) A laminated glass for projection image display, comprising:

[0033] 2 glass substrates; and

[0034] The laminated film for projection image display according to any one of (1) to (5) disposed between two glass substrates.

[0035] (7) A projection image display system comprising the projection image display laminated glass described in (6) and a projector that emits projection light toward the projection image display laminated glass.

[0036] Effects of the Invention

[0037] According to the present invention, it is possible to provide a laminated film for projection image display which has excellent impact resistance when sandwiched between two glass substrates and has excellent visibility of an image projected on the laminated glass for projection image display.

[0038] Furthermore, according to the present invention, it is possible to provide a laminated glass for projected image display and a projected image display system. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a diagram showing an example of a laminated film for projected image display in which the average value A is larger than the range of the present invention.

[0040] Figure 2 This is a diagram showing a laminated body obtained by bonding a laminated film for projected image display having an average value A larger than the range of the present invention onto a glass substrate.

[0041] Figure 3 This is a diagram showing an example of the laminated film for projected image display of the present invention.

[0042] Figure 4 This is a diagram showing an example of the laminated glass for projection image display of the present invention.

[0043] Figure 5 This is a diagram showing an example of a projection image display system according to the present invention. DETAILED DESCRIPTION

[0044] Hereinafter, the present invention will be described in detail.

[0045] The description of the constituent elements described below is made based on typical embodiments of the present invention, but the present invention is not limited to such embodiments.

[0046] In addition, in this specification, the numerical range expressed by "to" means a range including the numerical values ​​described before and after "to" as a lower limit value and an upper limit value.

[0047] Furthermore, in this specification, angles (e.g., angles of 90°) and their relationships (e.g., parallel, horizontal, vertical, etc.) include the permissible error range in the technical field to which the present invention belongs. For example, it refers to the range of ±10° less than the exact angle, and the error between the exact angle and the angle is preferably 5° or less, and more preferably 3° or less.

[0048] In this specification, when "selectivity" is mentioned for circularly polarized light, it means that the amount of light of any one of the right-handed circularly polarized light component and the left-handed circularly polarized light component of the light is greater than the amount of light of the other circularly polarized light component. Specifically, when "selectivity" is mentioned, the circular polarization degree of the light is preferably 0.3 or more, more preferably 0.6 or more, and further preferably 0.8 or more. It is particularly preferably substantially 1.0. Here, the circular polarization degree refers to the value represented by |IR-IL| / (IR+IL) when the intensity of the right-handed circularly polarized light component of the light is set to IR and the intensity of the left-handed circularly polarized light component is set to IL.

[0049] In this specification, when the "sense" of circularly polarized light is mentioned, it means right-handed circularly polarized light or left-handed circularly polarized light. Regarding the sense of circularly polarized light, when observing against the light toward the near side, the case where the front end of the electric field vector rotates clockwise with time is defined as right-handed circularly polarized light, and the case where it rotates counterclockwise is defined as left-handed circularly polarized light.

[0050] In this specification, the term "handedness" is sometimes used in relation to the twisting direction of the helix of cholesteric liquid crystal. When the twisting direction (handedness) of the helix of cholesteric liquid crystal is right, right-handed circularly polarized light is reflected and left-handed circularly polarized light is transmitted, and when the handedness is left, left-handed circularly polarized light is reflected and right-handed circularly polarized light is transmitted.

[0051] In this specification, "light" refers to visible light and natural light (non-polarized light) unless otherwise specified. Visible light is electromagnetic light with wavelengths visible to the human eye, and generally refers to light in the wavelength range of 380 to 780 nm.

[0052] In this specification, when simply expressed as "reflected light" or "transmitted light", it is used to mean including scattered light and diffracted light.

[0053] In addition, the polarization state of each wavelength of light can be measured using a spectroradiometer or a spectrometer equipped with a circular polarizer. At this time, the intensity of the light measured by the right-handed circular polarizer is equivalent to IR, and the intensity of the light measured by the left-handed circular polarizer is equivalent to IL. In addition, the circular polarizer can also be installed on a photometer or a spectrometer to measure. The right-handed circularly polarized light amount is measured by installing a right-handed circularly polarized light transmission plate and the left-handed circularly polarized light transmission plate is installed to measure the left-handed circularly polarized light amount, and the ratio can be measured.

[0054] In this specification, p-polarized light refers to polarized light that vibrates in a direction parallel to the incident plane of the light. The incident plane refers to a plane that is perpendicular to the reflection plane (laminated glass surface, etc.) and contains the incident light and the reflected light. The vibration plane of the electric field vector of p-polarized light is parallel to the incident plane.

[0055] In this specification, the front phase difference (in-plane retardation) is a value measured using AxoScan manufactured by Axometrics Co., Ltd. The measurement wavelength is 550 nm unless otherwise specified.

[0056] In this specification, "projection image" does not refer to the surrounding scenery such as the front, but refers to the image obtained by projecting light from the projector used. When observed from the perspective of the observer, the projection image can be observed as a virtual image floating at the front end of the projection image display part of the windshield.

[0057] In this specification, "screen image" refers to an image displayed on an image display device (imager) or an image drawn on an intermediate image screen etc. by the image display device. A screen image is a real image as opposed to a virtual image.

[0058] Both the image and the projected image may be monochrome images, images of two or more colors, or images of full colors.

[0059] The characteristic features of the laminated film for projected image display of the present invention include that the surface of the heat seal layer opposite to the support side has a predetermined roughness and the heat seal layer has a predetermined thickness.

[0060] The average value A of the arithmetic mean height Sa described later is the average value of the arithmetic mean height Sa measured in a wide range of observation fields, and indicates the degree of height of the large-period concavo-convex structure on the surface of the heat seal layer. Figure 1 and Figure 2 , a case where a multilayer film for projected image display having an average value A larger than the range of the present invention is attached to a glass substrate is described. Figure 1 The laminated film 100 for projection image display shown in the figure includes a support 102, a selective reflection layer 104 arranged on one surface of the support 102, and a heat seal layer 106 arranged on the other surface of the support 102. The surface 106A of the heat seal layer 106 on the side opposite to the support 102 has a large average value A and has a large periodic concavoconvex structure as shown in the figure. Figure 2 1 is a diagram showing a laminated film 100 for projected image display attached to a glass substrate 108. Figure 2 As shown, in Figure 1 When the surface 106A side of the heat seal layer 106 shown is attached to the glass substrate 108, the concavo-convex structure on the surface 106A is transferred to the surface on the opposite side (the surface on the support body 102 side of the heat seal layer 106), and as a result, the concavo-convex structure is also transferred to the surface of the selective reflection layer 104. When the surface of the selective reflection layer 104 has such a concavo-convex structure, it will cause deformation of the projection image, etc. In the present invention, the average value A is adjusted to be less than the specified value so as not to cause the above-mentioned problems.

[0061] Furthermore, the average value B of the arithmetic mean height S described later is the average value of the arithmetic mean height Sa measured in a narrow observation field, which indicates the degree of height of the small periodic concave-convex structure on the surface of the heat seal layer. When a heat seal layer having an average value B of more than a specified value is bonded to a glass substrate, due to the concave-convex structure, a small gap is generated between the glass substrate and the heat seal layer during bonding. Such a gap becomes an air escape channel for the air contained between the glass substrate and the heat seal layer during bonding, and as a result, bubbles are less likely to exist between the glass substrate and the heat seal layer, and the visual recognition of the projected image is improved. In the present invention, the average value B is adjusted to be more than a specified value to obtain the above-mentioned effect.

[0062] Furthermore, in the present invention, by setting the heat seal layer to have a predetermined thickness or more, the impact resistance of the laminated glass for projection image display obtained by using the laminated film for projection image display is improved.

[0063] Figure 3 Schematic diagram of an example of the projection image display laminated film of the present invention is shown in FIG.

[0064] Figure 3 The illustrated projection image display laminate film 10A includes a support 12, a selective reflection layer 14 disposed on one surface of the support 12, and a heat seal layer 16 disposed on the other surface of the support 12. The surface of the heat seal layer 16 on the side opposite to the support 12 side satisfies the necessary conditions of the average value A and the average value B described later.

[0065] Hereinafter, first, the average value A and the average value B, and the thickness of the heat seal layer, which are characteristic points of the present invention, will be described in detail.

[0066] In addition, the average value A and the average value B are values ​​obtained under measurement conditions with different ranges of the observation area. As described above, the average value A represents the height of large concave-convex structures such as corrugations on the surface of the heat seal layer, and the average value B represents the height of smaller concave-convex structures within a part of the corrugations on the surface of the heat seal layer.

[0067] When calculating the average value A, first calculate the arithmetic mean height Sa of the surface on the opposite side of the support body side of the heat seal layer of the projection image display laminated film. More specifically, Vertscan2.0 (Ryoka Systems Inc.) was used to measure the arithmetic mean height Sa within the range of the field of view size (3700 μm vertically × 4900 μm horizontally) at three different locations on the surface of the heat seal layer of the projection image display laminated film. In addition, the conditions for the above measurement are as follows.

[0068] Lens magnification: ×2.5

[0069] Tube magnification: ×0.5

[0070] Mode: Wave mode

[0071] The average value (arithmetic mean value) of the arithmetic mean heights Sa of the three locations calculated by the above-mentioned measurement is calculated, and the obtained value is defined as the average value A.

[0072] The average value A is below 40nm. Among them, from the perspective of the visual recognition of the image projected on the laminated glass obtained by using two glass substrates and the projection image display laminated film, the average value A is preferably below 30nm, more preferably below 20nm. The lower limit is not particularly limited, and more than 1nm can be cited, and more than 5nm can be cited.

[0073] When calculating the average value B, first calculate the arithmetic mean height Sa of the surface on the opposite side of the support body side of the heat seal layer of the projection image display laminated film. More specifically, Vertscan2.0 (Ryoka Systems Inc.) was used to measure the arithmetic mean height Sa within the range of the field of view size (180 μm in length × 240 μm in width) at three different locations on the surface of the heat seal layer of the projection image display laminated film. In addition, the conditions for the above measurement are as follows.

[0074] Lens magnification: ×50

[0075] Tube magnification: ×0.5

[0076] Mode: Wave mode

[0077] The average value (arithmetic mean value) of the arithmetic mean heights Sa of the three locations calculated by the above-mentioned measurement is calculated, and the obtained value is defined as the average value B.

[0078] The average value B is 7nm or more. Among them, from the perspective of the visual recognition of the image projected on the laminated glass obtained by using two glass substrates and the projection image display laminated film, the average value B is preferably 15nm or more, more preferably 20nm or more. The upper limit is not particularly limited, and the cases below 40nm and below 30nm are more.

[0079] The average thickness of the heat seal layer is 5 μm or more, preferably 7 μm or more, more preferably 9 μm or more, from the perspective of the excellent impact resistance of the laminated glass for projection image display obtained by using two glass substrates and the laminated film for projection image display. The upper limit is not particularly limited, but from the perspective of thin film, it is preferably 20 μm or less, more preferably 15 μm or less.

[0080] As a method for measuring the above-mentioned average thickness, the heat seal layer is cut out with a microtome to obtain a cross section, and the cross section is observed using a SEM (Scanning Electron Microscope). The thickness of the heat seal layer at three different locations is measured, and the average value (arithmetic mean) of the measured values ​​is calculated and used as the average thickness.

[0081] In addition, the heat-sealing layer may be a single-layer structure or a multi-layer structure of two or more layers.

[0082] When the heat seal layer is a multi-layer structure, the average value of the total thickness of the heat seal layer can be within the above range. That is, when the heat seal layer is composed of two layers, the heat seal layer 1 and the heat seal layer 2, the average value (average thickness) of the total thickness of the heat seal layer 1 and the heat seal layer 2 can be 5 μm or more.

[0083] Hereinafter, the members constituting the projected image display laminated film will be described in detail.

[0084] <Support body>

[0085] The support body is a component that supports the selective reflection layer and the heat sealing layer.

[0086] The front retardation Re of the support is not particularly limited, but is preferably 10 nm or less, and more preferably 5 nm or less.

[0087] The absolute value of the phase difference Rth in the thickness direction of the support is not particularly limited, but is preferably 40 nm or less, and more preferably 30 nm or less.

[0088] When the front retardation Re and the retardation Rth in the thickness direction are small, the polarization disorder caused by the support becomes small, which is preferable.

[0089] The constituent material of the support is not particularly limited, and examples thereof include resins such as cellulose acylate resins and acrylic resins, among which cellulose acylate resins are preferred, and cellulose triacetate resins or cellulose diacetate resins are more preferred.

[0090] The thickness of the support is not particularly limited, but is preferably 5.0 to 1000 μm, more preferably 10 to 250 μm, and even more preferably 15 to 90 μm.

[0091] <Selecting a reflective layer>

[0092] The selective reflection layer is a layer that selectively reflects light in wavelength. The selective reflection layer preferably exhibits selective reflection in a part of the visible light wavelength region. The selective reflection layer only needs to reflect light for displaying a projection image.

[0093] The multilayer film for projected image display may include only one selective reflection layer or may include two or more selective reflection layers.

[0094] In this specification, the selective reflection center wavelength λ of the selective reflection layer refers to a wavelength located at the centroid position of the reflection peak of the reflection spectrum measured in the normal direction of the selective reflection layer.

[0095] When the projection image display laminated film includes more than two selective reflection layers, the selective reflection center wavelengths of the two selective reflection layers may be the same or different, preferably different. By including more than two selective reflection layers with different selective reflection center wavelengths, ghosting can be reduced. For example, when the projection image display laminated film includes two selective reflection layers, the selective reflection center wavelengths of the two layers are preferably different by more than 60nm, more preferably different by more than 80nm, and further preferably different by more than 100nm.

[0096] When two or more selective reflection layers are used, it is preferred to use a selective reflection layer having a selective reflection center wavelength of 500 to 650 nm (preferably 500 to 600 nm) and a selective reflection layer having a selective reflection center wavelength of 650 to 900 nm (preferably 650 to 780 nm).

[0097] The selective reflection layer is preferably a polarized light reflection layer. The polarized light reflection layer is a layer that selectively reflects linearly polarized light, circularly polarized light, or elliptically polarized light.

[0098] The polarized light reflecting layer is preferably a circularly polarized light reflecting layer or a linearly polarized light reflecting layer. The circularly polarized light reflecting layer is a layer that reflects circularly polarized light of any one hand and transmits circularly polarized light of another hand at a selective reflection center wavelength.

[0099] The linearly polarized light reflecting layer is a layer that reflects linearly polarized light in one polarization direction at a selective reflection center wavelength and transmits linearly polarized light in a polarization direction orthogonal to the polarization direction.

[0100] The polarized light reflecting layer can transmit polarized light that is not reflected, and can also transmit a portion of light in the wavelength region where the selective reflecting layer reflects.

[0101] As the selective reflection layer of the circularly polarized light reflection layer, a cholesteric liquid crystal layer is preferable.

[0102] (Cholesteric Liquid Crystal Layer)

[0103] The cholesteric liquid crystal layer is a layer in which a cholesteric liquid crystal phase is fixed.

[0104] The cholesteric liquid crystal layer may be any layer that maintains the orientation of the liquid crystal compound that has become a cholesteric liquid crystal phase. Typically, the cholesteric liquid crystal layer may be any layer that is formed by polymerizing and curing the polymerizable liquid crystal compound into a cholesteric liquid crystal phase by ultraviolet irradiation or heating, etc. to form a layer without fluidity, and at the same time, a layer in a state in which the orientation morphology is not changed by an external field or external force.

[0105] In addition, in the cholesteric liquid crystal layer, as long as the optical properties of the cholesteric liquid crystal phase are maintained in the layer, the liquid crystal compound in the layer may no longer exhibit liquid crystallinity. For example, the polymerizable liquid crystal compound may be converted to a high molecular weight by a curing reaction and no longer exhibit liquid crystallinity.

[0106] It is known that a cholesteric liquid crystal layer exhibits circularly polarized light selective reflection, which selectively reflects circularly polarized light of one of right-handed circularly polarized light and left-handed circularly polarized light, and transmits circularly polarized light of the other direction.

[0107] As a layer in which a cholesteric liquid crystal phase exhibiting circularly polarized light selective reflectivity is fixed, many layers formed of a composition containing a polymerizable liquid crystal compound are known so far, and these conventional techniques can be referred to for the cholesteric liquid crystal layer.

[0108] The selective reflection center wavelength λ of the cholesteric liquid crystal layer depends on the pitch P (= period of the spiral) of the spiral structure in the cholesteric phase, and follows the relationship between the average refractive index n of the cholesteric liquid crystal layer and λ=n×P. As can be seen from this formula, the selective reflection center wavelength can be adjusted by adjusting the n value and the P value.

[0109] The selective reflection central wavelength and half-peak width of the cholesteric liquid crystal layer can be obtained as follows.

[0110] When the transmission spectrum of the cholesteric liquid crystal layer is measured using a spectrophotometer UV3150 (manufactured by SHIMADZU CORPORATION) (measured from the normal direction of the cholesteric liquid crystal layer), a peak of transmittance decrease can be observed in the selective reflection band. In the two wavelengths of the intermediate (average) transmittance between the minimum transmittance of the peak and the transmittance before the decrease, if the value of the wavelength on the short wavelength side is set to λl (nm) and the value of the wavelength on the long wavelength side is set to λh (nm), the selective reflection center wavelength λ and the half-peak width Δλ can be expressed by the following formula.

[0111] λ=(λl+λh) / 2

[0112] Δλ=(λh-λl)

[0113] The selective reflection center wavelength obtained as described above substantially coincides with the wavelength located at the center of gravity of the reflection peak of the circularly polarized light reflection spectrum measured in the normal direction of the cholesteric liquid crystal layer.

[0114] The pitch of the cholesteric liquid crystal phase depends on the type of chiral reagent used together with the polymerizable liquid crystal compound or its added concentration, so by adjusting these, the desired pitch can be obtained. In addition, the method for measuring the handedness or pitch of the spiral can be used in "Introduction to Liquid Crystal Chemistry Experiments", edited by the Liquid Crystal Society of Japan, published by Sigma, published in 2007, page 46 and "Liquid Crystal Handbook", Liquid Crystal Handbook Editorial Committee, Maruzen page 196.

[0115] When the projection image display laminated film includes two or more cholesteric liquid crystal layers, the projection image display laminated glass is preferably arranged in order from the cholesteric liquid crystal layer having the shortest selective reflection center wavelength when viewed from the viewing side (interior side).

[0116] As each cholesteric liquid crystal layer, a cholesteric liquid crystal layer having a right or left handedness of the spiral can be used. The handedness of the reflected circularly polarized light of the cholesteric liquid crystal layer is consistent with the handedness of the spiral. The handedness of the spirals of the cholesteric liquid crystal layers having different reflection center wavelengths can be all the same, or can include different handednesses, preferably the same.

[0117] Furthermore, the projection image display laminated film preferably does not include a cholesteric liquid crystal layer having a different helical handedness as a cholesteric liquid crystal layer that exhibits selective reflection in the same or overlapping wavelength regions. This is to prevent the transmittance in a specific wavelength region from decreasing to, for example, less than 50%.

[0118] Regarding the half-peak width Δλ (nm) of the selective reflection band showing the selective reflection, Δλ depends on the birefringence Δn of the liquid crystal compound and the above-mentioned pitch P, and follows the relationship of Δλ=Δn×P. Therefore, the control of the width of the selective reflection band can be performed by adjusting Δn. The adjustment of Δn can be performed by adjusting the type and mixing ratio of the polymerizable liquid crystal compound or controlling the temperature when the alignment is fixed.

[0119] In order to form a cholesteric liquid crystal layer with the same selective reflection center wavelength, multiple cholesteric liquid crystal layers with the same pitch P and the same helical handedness can be stacked. By stacking cholesteric liquid crystal layers with the same pitch P and the same helical handedness, the selectivity of circularly polarized light can be improved at a specific wavelength.

[0120] When stacking multiple cholesteric liquid crystal layers, separately produced cholesteric liquid crystal layers may be stacked using an adhesive or the like, or a liquid crystal composition containing a polymerizable liquid crystal compound or the like may be directly coated on the surface of the aforementioned cholesteric liquid crystal layer formed by the method described later and the alignment and fixing steps may be repeated.

[0121] The thickness of the cholesteric liquid crystal layer is preferably 0.05 to 10 μm, more preferably 0.1 to 8.0 μm, and further preferably 0.2 to 6.0 μm.

[0122] Furthermore, the total thickness of the cholesteric liquid crystal layer in the projection image display laminated film is preferably 2.0 to 30 μm, more preferably 2.5 to 25 μm, and further preferably 3.0 to 20 μm.

[0123] (Method for producing a cholesteric liquid crystal layer)

[0124] Hereinafter, the materials and method for producing the cholesteric liquid crystal layer will be described.

[0125] Examples of materials for forming the cholesteric liquid crystal layer include a liquid crystal composition containing a polymerizable liquid crystal compound and a chiral agent (optically active compound). The liquid crystal composition may further contain a surfactant, a polymerization initiator, and the like as necessary.

[0126] The above-mentioned liquid crystal composition prepared by mixing these components and dissolving them in a solvent is applied onto a support, an alignment layer, or a cholesteric liquid crystal layer serving as an underlayer, and after cholesteric alignment aging, the liquid crystal composition is cured to fix the mixture, thereby forming a cholesteric liquid crystal layer.

[0127] The polymerizable liquid crystal compound may be a rod-shaped liquid crystal compound or a disc-shaped liquid crystal compound, and is preferably a rod-shaped liquid crystal compound.

[0128] Examples of rod-shaped polymerizable liquid crystal compounds that form the cholesteric liquid crystal layer include rod-shaped nematic liquid crystal compounds. Preferred rod-shaped nematic liquid crystal compounds include azomethines, azoxyls, cyanobiphenyls, cyanophenyl esters, benzoates, cyclohexanecarboxylic acid phenyl esters, cyanophenylcyclohexanes, cyano-substituted phenylpyrimidines, alkoxy-substituted phenylpyrimidines, phenyldioxanes, tolans, and alkenylcyclohexylbenzonitriles.

[0129] The polymerizable liquid crystal compound is obtained by introducing a polymerizable group into a liquid crystal compound.

[0130] Examples of polymerizable groups include unsaturated polymerizable groups, epoxy groups, and aziridine groups, preferably unsaturated polymerizable groups, more preferably ethylenically unsaturated polymerizable groups. The polymerizable groups can be introduced into the molecules of the liquid crystal compound by various methods. The number of polymerizable groups possessed by the polymerizable liquid crystal compound is preferably 1 to 6, more preferably 1 to 3.

[0131] Examples of polymerizable liquid crystal compounds include Makromol. Chem., Vol. 190, p. 2255 (1989), Advanced Materials 5, page 107 (1993), U.S. Patent No. 4,683,327, U.S. Patent No. 5,622,648, U.S. Patent No. 5,770,107, International Publication No. 95 / 022,586, International Publication No. 95 / 024455, International Publication No. 97 / 000600, International Publication No. 98 / 023580, International Publication No. 98 / 052905, Japanese Patent Application Publication No. 1-272551, Japanese Patent Application Publication No. 6-016616, Japanese Patent Application Publication No. 7-110469, Japanese Patent Application Publication No. 11-080081 and Japanese Patent Application Publication No. 2001-328973.

[0132] The polymerizable liquid crystal compound may be used alone or in combination of two or more.

[0133] The content of the polymerizable liquid crystal compound in the liquid crystal composition is preferably 80 to 99.9% by mass, more preferably 85 to 99.5% by mass, and even more preferably 90 to 99% by mass, based on the solid content mass (mass excluding the solvent) of the liquid crystal composition.

[0134] The chiral agent has the function of inducing a helical structure of a cholesteric liquid crystal phase. The handedness or helical pitch of the induced helix varies depending on the compound, so the chiral compound can be selected according to the purpose.

[0135] Chiral reagent is not particularly limited, and known compounds can be used. As chiral reagent, liquid crystal device handbook (Chapter 3, 4-3, TN, STN chiral reagent, 199 pages, Japan Society for the Promotion of Science 142nd Committee compiled, 1989), Japanese Patent Publication No. 2003-287623, Japanese Patent Publication No. 2002-302487, Japanese Patent Publication No. 2002-080478, Japanese Patent Publication No. 2002-080851, Japanese Patent Publication No. 2010-181852 and Japanese Patent Publication No. 2014-034581 can be enumerated. The compound recorded in each bulletin.

[0136] Chiral reagents generally contain an asymmetric carbon atom, but axially asymmetric compounds or surface asymmetric compounds not containing an asymmetric carbon atom can also be used as chiral reagents.

[0137] Examples of the axially asymmetric compound or the surface asymmetric compound include binaphthyl, helicene, p-xylene dimer, and derivatives thereof.

[0138] The chiral agent may have a polymerizable group. When both the chiral agent and the liquid crystal compound have a polymerizable group, a polymer having a repeating unit derived from the polymerizable liquid crystal compound and a repeating unit derived from the chiral agent can be formed by the polymerization reaction of the polymerizable chiral agent and the polymerizable liquid crystal compound. In this manner, the polymerizable group possessed by the polymerizable chiral agent is preferably a group of the same type as the polymerizable group possessed by the polymerizable liquid crystal compound. Therefore, the polymerizable group of the chiral agent is also preferably an unsaturated polymerizable group, an epoxy group or an aziridine group, more preferably an unsaturated polymerizable group, and further preferably an ethylenically unsaturated polymerizable group.

[0139] Furthermore, the chiral agent may also be a liquid crystal compound.

[0140] As the chiral reagent, preferably used are isosorbide derivatives, isomannide derivatives, binaphthyl derivatives, etc. As the isosorbide derivative, commercially available products such as LC-756 manufactured by BASF can be used.

[0141] The chiral reagent may be used alone or in combination of two or more.

[0142] The content of the chiral agent in the liquid crystal composition is preferably 0.01 to 200 mol %, more preferably 1 to 30 mol %, based on the total molar amount of the polymerizable liquid crystal compound.

[0143] The liquid crystal composition preferably contains a polymerization initiator. In the embodiment in which the polymerization reaction is carried out by ultraviolet irradiation, the polymerization initiator used is preferably a photopolymerization initiator capable of initiating the polymerization reaction by ultraviolet irradiation.

[0144] The polymerization initiator may be used alone or in combination of two or more.

[0145] The content of the photopolymerization initiator in the liquid crystal composition is preferably 0.1 to 20% by mass, more preferably 0.5 to 5% by mass, based on the content of the polymerizable liquid crystal compound.

[0146] The liquid crystal composition preferably contains a solvent. As the solvent, an organic solvent is preferred.

[0147] The organic solvent is not particularly limited, and examples thereof include ketones, alkyl halides, amides, sulfoxides, heterocyclic compounds, hydrocarbons, esters, and ethers.

[0148] The liquid crystal composition may contain a crosslinking agent to increase the film strength after curing and improve durability. As the crosslinking agent, a crosslinking agent that is cured by ultraviolet rays, heat, moisture, etc. can be preferably used.

[0149] The content of the crosslinking agent in the liquid crystal composition is preferably 3 to 20% by mass, more preferably 5 to 15% by mass, based on the content of the polymerizable liquid crystal compound.

[0150] The liquid crystal composition preferably contains an alignment control agent.

[0151] Examples of the alignment control agent include fluoro(meth)acrylate polymers described in paragraphs 1 to 3 of JP-A-2007-272185, compounds represented by formulas (I) to (IV) described in paragraphs 1 to 3 of JP-A-2012-203237, and compounds described in JP-A-2013-113913.

[0152] The content of the alignment control agent in the liquid crystal composition is preferably 0.01 to 10% by mass, more preferably 0.01 to 5% by mass, based on the total mass of the polymerizable liquid crystal compound.

[0153] The liquid crystal composition may further contain additives such as a surfactant, a polymerization inhibitor, an antioxidant, an ultraviolet absorber, a light stabilizer, a colorant, and metal oxide particles as necessary.

[0154] Regarding the cholesteric liquid crystal layer, a liquid crystal composition in which a polymerizable liquid crystal compound and a chiral reagent, a polymerization initiator and a surfactant which are further added as needed are dissolved in a solvent is applied to a support, an orientation layer or a previously prepared cholesteric liquid crystal layer, and the like, and the coating is dried to obtain a coating film, and the coating film is irradiated with activating light to polymerize the cholesteric liquid crystal composition, thereby forming a cholesteric liquid crystal layer in which the cholesterol regularity is fixed.

[0155] In addition, a stacked film composed of a plurality of cholesteric liquid crystal layers can be formed by repeating the above-mentioned manufacturing steps of the cholesteric liquid crystal layers.

[0156] The coating method of the liquid crystal composition is not particularly limited, and examples thereof include wire bar coating, curtain coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spin coating, dip coating, spray coating, and slide coating.

[0157] Furthermore, the method may be implemented by transferring a liquid crystal composition separately applied on a support.

[0158] The applied liquid crystal composition is heated to align the polymerizable liquid crystal compound.

[0159] The heating temperature is preferably 200° C. or lower, more preferably 130° C. or lower. By this alignment treatment, an optical film is obtained in which the polymerizable liquid crystal compound is twistedly aligned so as to have a helical axis in a direction substantially perpendicular to the film surface.

[0160] The liquid crystal composition can be cured by further polymerizing the aligned liquid crystal compound. The polymerization may be either thermal polymerization or photopolymerization by light irradiation, and photopolymerization is preferred.

[0161] Ultraviolet rays are preferably used for light irradiation. The irradiation energy is preferably 20 mJ / cm 2 ~50J / cm 2 , more preferably 100 to 1,500 mJ / cm 2 .

[0162] In order to promote the photopolymerization reaction, light irradiation may be performed under heating conditions or under a nitrogen atmosphere. The wavelength of the irradiated ultraviolet rays is preferably 350 to 430 nm.

[0163] (Linearly polarized light reflection layer)

[0164] As the selective reflection layer, a linearly polarized light reflection layer can be used.

[0165] As a linearly polarized light reflecting layer, a polarizer obtained by laminating thin films having different refractive index anisotropy can be mentioned, for example.

[0166] As a polarizer obtained by laminating thin films having different refractive index anisotropies, for example, a polarizer described in Japanese Unexamined Patent Publication No. 9-506837 can be used.

[0167] As the polarizer obtained by laminating thin films having different refractive index anisotropies, a commercially available product can be used. The commercially available product can be a laminate of a reflection-type polarizing plate and a dummy support.

[0168] As a commercial item, the commercially available optical film etc. which are marketed as DBEF (registered trademark) (produced by 3M Company) and APF (Advanced Polarizing Film (produced by 3M Company)) are mentioned, for example.

[0169] <Heat seal layer>

[0170] As described above, the heat seal layer has a function of ensuring adhesion with the glass substrate.

[0171] The heat seal layer is a layer for physically bonding the projection image display laminate film and the glass substrate.

[0172] The heat seal layer preferably comprises a thermoplastic resin.

[0173] The thermoplastic resin is preferably a resin having good affinity and adhesion to the glass substrate, preferably a resin selected from the group consisting of polyvinyl acetal resins represented by polyvinyl butyral (PVB) resins, ethylene-vinyl acetate copolymers, and chlorine-containing resins, and more preferably a polyvinyl acetal resin.

[0174] As the thermoplastic resin, polyvinyl butyral or ethylene-vinyl acetate copolymer is preferred, and polyvinyl butyral is more preferred.

[0175] Polyvinyl butyral can be obtained by acetalizing polyvinyl alcohol with butyraldehyde.

[0176] The degree of acetalization of polyvinyl butyral is not particularly limited, but is preferably 40% or more, more preferably 60% or more. The upper limit is not particularly limited, but is preferably 85% or less, more preferably 75% or less.

[0177] Polyvinyl alcohol used for the synthesis of polyvinyl butyral is generally obtained by saponifying polyvinyl acetate, and polyvinyl alcohol having a saponification degree of 80 to 99.8 mol % is generally used.

[0178] Furthermore, the degree of polymerization of the polyvinyl alcohol is preferably 200 to 3,000.

[0179] Thermoplastic resin is preferably the main component of the heat seal layer. In addition, the main component refers to a component that accounts for 50% by mass or more of the total mass of the heat seal layer.

[0180] More specifically, the content of the thermoplastic resin in the heat seal layer is preferably 60 to 99% by mass, more preferably 70 to 97% by mass, based on the total mass of the heat seal layer.

[0181] The heat seal layer may contain inorganic particles.

[0182] The inorganic particles contained in the heat seal layer are preferably inorganic oxide particles, more preferably silica particles, alumina particles, titania particles or zirconia particles, and still more preferably silica particles.

[0183] The inorganic particles are preferably composed of primary particles and form secondary particles composed of aggregation of the primary particles.

[0184] The average primary particle size of the inorganic particles is not particularly limited, but is preferably 5 to 50 nm, more preferably 5 to 15 nm.

[0185] The average secondary particle size of the inorganic particles is not particularly limited, but is preferably 100 to 500 nm.

[0186] The content of inorganic particles in the heat seal layer is not particularly limited, and is preferably 1% by mass or more, more preferably 9% by mass or more, relative to the total mass of the heat seal layer. The upper limit is not particularly limited, and is preferably 40% by mass or less, more preferably 30% by mass or less.

[0187] In addition, since the content of the inorganic particles in the heat seal layer may affect the average value B, it is preferably adjusted within the above range.

[0188] The average primary particle size of the inorganic particles is measured by transmission electron microscopy. Specifically, for 50 randomly selected primary particles, the diameter of the circle circumscribed to the primary particles is obtained, and the arithmetic average is taken as the average primary particle size. The observation magnification of the transmission electron microscope is set to any magnification that can distinguish the primary particle size between 500,000 times and 5,000,000 times.

[0189] The average secondary particle size is a value measured by true spherical fitting (refractive index 1.46) using a laser diffraction scattering particle size distribution measuring device. As a measuring device, for example, Microtrac MT3000 manufactured by Microtrac BEL Corp. can be used.

[0190] The heat seal layer may contain a leveling agent. When the heat seal layer contains a leveling agent, the surface of the heat seal layer is smoothed, and the average value A can be reduced.

[0191] As the leveling agent, a known leveling agent can be used, and examples thereof include surfactants, among which fluorine-based surfactants and silicone-based surfactants are preferred.

[0192] The fluorine content in the fluorine-based surfactant is preferably 3 to 40% by mass, more preferably 5 to 30% by mass, and further preferably 7 to 25% by mass. Fluorine-based surfactants having a fluorine content within this range are effective in terms of uniformity of coating film thickness and liquid saving.

[0193] The content of the leveling agent in the heat seal layer is not particularly limited, but is preferably 0.005 to 0.5% by mass, more preferably 0.01 to 0.1% by mass, based on the total mass of the heat seal layer.

[0194] As described above, the heat seal layer shows predetermined average values ​​A and average values ​​B on the surface opposite to the support side.

[0195] The water contact angle of the surface of the heat seal layer on the side opposite to the support body side is not particularly limited, but is preferably 90° or less, more preferably 80° or less, and further preferably 70° or less, from the perspective of the superior impact resistance of the laminated glass for projection image display obtained by using two glass substrates and the laminated film for projection image display. The lower limit is not particularly limited, but is more often 10° or more, and more often 30° or more.

[0196] The method for measuring the water contact angle is as follows.

[0197] First, using a contact angle measuring instrument CA-X (manufactured by Kyowa Interface Science Co., Ltd.) at 3 different locations on the surface of the heat seal layer of the projection image display laminated film, a droplet of 1.0 mm in diameter was made on the tip of a needle using pure water under an environment of 20°C and 65% RH, and the droplet was made in contact with the surface of the heat seal layer. The angle on the pure water side was measured by the angle formed by the tangent line to the pure water surface and the heat seal layer surface at the point where the heat seal layer surface and the pure water contacted 25 seconds after the heat seal layer surface and the pure water contacted, and the average value thereof was taken as the water contact angle of the projection image display laminated film.

[0198] (Method for forming heat seal layer)

[0199] The method for forming the heat seal layer is not particularly limited as long as a heat seal layer having the above average values ​​A and B and an average thickness within the prescribed ranges can be formed.

[0200] Among them, a method using a heat seal layer forming composition containing a thermoplastic resin and inorganic particles is preferred. More specifically, a method of coating the heat seal layer forming composition on a support to form a heat seal layer is preferred.

[0201] The contents of the thermoplastic resin and the inorganic particles in the heat seal layer forming composition are preferably adjusted to the contents of the thermoplastic resin and the inorganic particles to be contained in the heat seal layer.

[0202] The heat seal layer forming composition may contain the above-mentioned leveling agent.

[0203] The content of the leveling agent in the heat seal layer forming composition is preferably adjusted to a content of the leveling agent in the heat seal layer.

[0204] From the viewpoint of coating properties, the heat seal layer forming composition preferably contains a solvent.

[0205] The type of solvent is not particularly limited, and examples thereof include water and organic solvents, and organic solvents are preferred. Examples of the organic solvent include ketones, alkyl halides, amides, sulfoxides, heterocyclic compounds, hydrocarbons, esters, and ethers.

[0206] The average value A of the heat seal layer can be adjusted by adjusting the solid content concentration in the heat seal layer forming composition. From the perspective of being able to lower the average value A, the solid content concentration in the heat seal layer forming composition is preferably 3% by mass or more, more preferably 5% by mass or more, relative to the total mass of the heat seal layer forming composition. The upper limit is not particularly limited, but is preferably 30% by mass or less, more preferably 20% by mass or less.

[0207] When the heat seal layer forming composition does not contain a leveling agent, the solid content concentration in the heat seal layer forming composition is preferably 16% by mass or more based on the total mass of the heat seal layer forming composition in order to lower the average value A.

[0208] The solid content is the component that forms the heat seal layer except the solvent. Even if the component is in liquid form, it is calculated as the solid content.

[0209] The coating method of the heat seal layer forming composition is not particularly limited, and examples thereof include wire rod coating, curtain coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spin coating, dip coating, spray coating, and slide coating.

[0210] The coating film obtained by application may be subjected to a drying treatment as necessary.

[0211] The drying treatment may be a heating treatment. The heating temperature in the heating treatment is not particularly limited, but is preferably 50 to 150° C., more preferably 60 to 140° C. The heating time is not particularly limited, but is preferably 0.5 to 20 minutes, more preferably 0.5 to 10 minutes.

[0212] The surface of the formed heat seal layer (the surface on the side opposite to the support) may be subjected to surface treatment as necessary.

[0213] For example, in order to reduce the water contact angle of the heat seal layer surface, the heat seal layer surface may be subjected to a hydrophilic treatment. Examples of the hydrophilic treatment include plasma treatment, ultraviolet irradiation treatment, corona treatment, and electron beam irradiation treatment, and corona treatment is preferred.

[0214] The conditions for the hydrophilization treatment are appropriately selected depending on the type of treatment to be performed, and are preferably adjusted to fall within the range of the water contact angle of the surface of the heat seal layer.

[0215] Furthermore, the surface of the heat seal layer may be subjected to a roughening treatment. By performing the roughening treatment, the range of the average value A and the average value B (especially the average value B) can be adjusted.

[0216] As roughening treatment, grinding and sandblasting can be cited. Grinding is a treatment in which a substrate forms a concave-convex shape on the surface of the object to be ground using a disk or belt holding abrasive grains. Sandblasting is a treatment in which abrasive grains are sprayed to form a concave-convex shape on the surface of the object to be sprayed.

[0217] <Other parts>

[0218] The laminated film for projected image display may include other members in addition to the above-mentioned members (support, selective reflection layer and heat seal layer).

[0219] (Orientation Layer)

[0220] The multilayer film for projected image display may include an alignment layer. The alignment layer can function as a base layer of the cholesteric liquid crystal layer and the retardation layer described later.

[0221] The alignment layer can be provided by a method such as rubbing treatment of an organic compound such as a polymer, oblique deposition of an inorganic compound, formation of a layer having microgrooves, and accumulation of an organic compound using the Langmuir-Blodgett method (LB film).

[0222] Furthermore, an alignment layer that generates an alignment function by applying an electric field, applying a magnetic field, or irradiating light may be used.

[0223] In particular, it is preferred that the alignment layer composed of a polymer is subjected to a rubbing treatment and then a liquid crystal composition is applied to the rubbing treated surface. The rubbing treatment can be performed by rubbing the surface of the polymer layer with paper or cloth in a predetermined direction.

[0224] Examples of the polymer include polyimide, polyvinyl alcohol, polyester, polyarylate, polyamideimide, polyetherimide, polyamide, and modified polyamide.

[0225] The thickness of the alignment layer is preferably 0.01 to 5.0 μm, more preferably 0.05 to 2.0 μm.

[0226] (Phase difference layer)

[0227] The multilayer film for projected image display may include a phase difference layer.

[0228] The phase difference layer adds a phase difference (optical path difference) to two orthogonal polarized light components to convert the state of incident polarized light.

[0229] The retardation layer is preferably provided so as to be located on the visual recognition side with respect to all the selective reflection layers (cholesteric liquid crystal layers) when in use.

[0230] The phase difference layer is preferably disposed between the support and the selective reflection layer.

[0231] Examples of the phase difference layer include a stretched polycarbonate film, a stretched norbornene polymer film, an oriented transparent film containing inorganic particles having birefringence such as strontium carbonate, a thin film obtained by obliquely depositing an inorganic dielectric on a support, and a film obtained by uniaxially oriented and fixed liquid crystal compounds.

[0232] As a phase difference layer, it is preferably a film in which the polymerizable liquid crystal compound is uniaxially oriented and oriented. For example, the phase difference layer can be formed as follows: a liquid crystal composition containing a polymerizable liquid crystal compound is coated on the surface of a pseudo support or an orientation layer, and the polymerizable liquid crystal compound in the coating film is formed into a nematic orientation in a liquid crystal state, and then fixed by curing. Regarding the formation of the phase difference layer at this time, except that a chiral agent is not added to the liquid crystal composition, it can be carried out in the same manner as the formation of the above-mentioned cholesteric liquid crystal layer. Among them, when the nematic orientation is performed after the liquid crystal composition is applied, the heating temperature is preferably 50 to 120°C, and more preferably 60 to 100°C.

[0233] In the case where the phase difference layer is a phase difference layer that converts linear polarized light into circular polarized light, the phase difference layer is preferably composed of an object that provides a front phase difference of λ / 4, and can also be composed of an object that provides a front phase difference of 3λ / 4. And, it is sufficient as long as the angle of the slow axis is arranged in a direction that converts the incident linear polarized light into circular polarized light.

[0234] In this case, the retardation layer preferably has a front retardation at a wavelength of 550 nm in the range of 100 to 450 nm, more preferably in the range of 120 to 200 nm or 300 to 400 nm.

[0235] The thickness of the retardation layer is not particularly limited, but is preferably 0.2 to 300 μm, and more preferably 0.4 to 150 μm.

[0236] The thickness of the retardation layer formed of the liquid crystal composition is not particularly limited, but is preferably 0.2 to 10 μm, and more preferably 0.4 to 5.0 μm.

[0237] (Polarization conversion layer)

[0238] The laminated film for projected image display may include a polarization conversion layer.

[0239] The polarization conversion layer is preferably disposed on the side of the selective reflection layer opposite to the support side.

[0240] By providing a polarized light conversion layer, the applicability of polarized sunglasses can be improved in a projection image display system that projects p-polarized light. The above mechanism is described in detail in paragraph 0102 of International Publication No. 2020 / 080355.

[0241] Examples of the polarization conversion layer include a layer in which the helical alignment structure of a liquid crystal compound is fixed.

[0242] As a layer obtained by fixing the helical orientation structure of the liquid crystal compound, when the pitch number of the helical structure of the polarization conversion layer is set to x and the film thickness of the polarization conversion layer is set to y (unit μm), the polarization conversion layer is preferably a layer that satisfies the following relationship expressions (i) and (ii).

[0243] (i) 0.3 ≤ x ≤ 2.0

[0244] (ii) 0.5 ≤ y ≤ 7.0

[0245] As with the cholesteric liquid crystal layer, the pitch of the helical structure (helical pitch 1) refers to the length in the direction of the helical axis when the director of the liquid crystal compound constituting the helical orientation structure rotates 360 degrees. In the polarization conversion layer obtained by fixing the helical orientation structure of the liquid crystal compound, 1 pitch when the director of the liquid crystal compound rotates 360 degrees is taken as the pitch number 1.

[0246] The polarization conversion layer obtained by fixing the helical orientation structure of the liquid crystal compound preferably has a pitch number of 0.3 to 2.0 and a film thickness of 0.5 to 7.0 μm.

[0247] (Adhesive layer)

[0248] The laminated film for projected image display may include an adhesive layer. The adhesive layer is used to ensure interlayer adhesion.

[0249] The position of the adhesive layer is not particularly limited, and examples thereof include between cholesteric liquid crystal layers, between the selective reflection layer and the retardation layer, and between the selective reflection layer and the polarization conversion layer.

[0250] The adhesive layer may be formed of an adhesive.

[0251] As adhesives, there are hot melt type, thermosetting type, light curing type, reaction curing type, and pressure sensitive adhesive type which does not require curing.

[0252] The thickness of the adhesive layer is preferably 0.5 to 10 μm, more preferably 1.0 to 5.0 μm.

[0253] The thickness of the adhesive layer formed using the OCA tape is preferably 10 to 50 μm, more preferably 15 to 30 μm.

[0254] <Laminated glass for projection image display>

[0255] The above-mentioned laminated film for projection image display can be preferably used as laminated glass for projection image display by being sandwiched between two glass substrates.

[0256] The laminated glass for projection image display can be preferably applied to window glass and windshield of general transportation vehicles such as automobiles and trains, airplanes, ships, two-wheeled vehicles and amusement facilities. The laminated glass for projection image display is preferably used as a front windshield or windshield located in the front of the vehicle in the direction of travel.

[0257] Figure 4 Schematic diagram of an example of the laminated glass for projection image display of the present invention is shown in FIG.

[0258] Figure 4 The laminated glass 20 for projection image display shown includes a first glass substrate 22, a laminated film 10A for projection image display, an intermediate film 24, and a second glass substrate 26. In addition, the heat seal layer in the laminated film 10A for projection image display is arranged on the first glass substrate 22 side.

[0259] Hereinafter, the components constituting the laminated glass for projected image display will be described in detail.

[0260] In addition, the laminated film for projected image display is as described above, and the description thereof is omitted.

[0261] (First Glass Substrate and Second Glass Substrate)

[0262] The first glass substrate and the second glass substrate may be glass substrates generally used for laminated glass, for example, glass substrates having a visible light transmittance of 80% or less such as 73% and 76% such as green glass with high heat shielding properties may be used.

[0263] The thickness of the first glass substrate and the second glass substrate is not particularly limited, but is preferably 0.5 to 5.0 mm, and more preferably 1.0 to 3.0 mm.

[0264] The first glass substrate and the second glass substrate may be made of the same material or have different thicknesses.

[0265] (Intermediate film)

[0266] Any known interlayer film used for laminated glass of vehicles can be used as the interlayer film, and for example, a resin film containing a resin selected from the group consisting of polyvinyl butyral (PVB), ethylene-vinyl acetate copolymer, and chlorine-containing resin can be used.

[0267] The above resin is preferably a main component of the interlayer film. In addition, the main component refers to a component that accounts for 50% by mass or more of the interlayer film.

[0268] Among these resins, polyvinyl butyral or ethylene-vinyl acetate copolymer is preferred, and polyvinyl butyral is more preferred.

[0269] Polyvinyl butyral can be obtained by acetalizing polyvinyl alcohol with butyraldehyde.

[0270] The degree of acetalization of polyvinyl butyral is not particularly limited, but is preferably 40% or more, more preferably 60% or more. The upper limit is not particularly limited, but is preferably 85% or less, more preferably 75% or less.

[0271] Polyvinyl alcohol used for the synthesis of polyvinyl butyral is generally obtained by saponifying polyvinyl acetate, and polyvinyl alcohol having a saponification degree of 80 to 99.8 mol % is generally used.

[0272] Furthermore, the degree of polymerization of the polyvinyl alcohol is preferably 200 to 3,000.

[0273] The method for producing the laminated glass for projection image display of the present invention is not particularly limited, and a known method can be adopted.

[0274] Generally, it can be produced by sandwiching an interlayer film for laminated glass between two glass substrates, repeating heating treatment and pressurizing treatment (treatment using a rubber roller, etc.) several times, and finally performing heating treatment under pressurized conditions using an autoclave or the like.

[0275] As an example of a method for manufacturing laminated glass for projection image display comprising a laminate film for projection image display and an intermediate film, there can be cited a method in which a laminate obtained by bonding a heat-sealed layer of a laminate film for projection image display to a first glass substrate is laminated with a second glass substrate via an intermediate film and subjected to a heat treatment and / or a pressurization treatment.

[0276] <Projection image display system>

[0277] The projection image display system of the present invention is a system including the above-mentioned laminated glass for projection image display and a projector.

[0278] Figure 5 An example of a projection image display system is shown in FIG.

[0279] Figure 5 The projected image display system 30 shown includes a projected image display laminated glass 32 and a projector 34. The projected image display system 30 is used in a vehicle such as a passenger car, for example.

[0280] The laminated glass 32 for projected image display includes a first glass substrate 22 , a projected image display laminated film 10B, an intermediate film 24 , and a second glass substrate 26 .

[0281] The multilayer film 10B for projected image display includes a heat seal layer, a support, a phase difference layer, and a selective reflection layer in this order. The multilayer film 10B for projected image display is bonded to the first glass substrate 22 via the heat seal layer.

[0282] In the projection image display system 30 , the projector 34 emits p-polarized projection light, and the projection image display laminated glass 32 reflects the p-polarized light, thereby displaying an image.

[0283] Specifically, in the projection image display laminated glass 32, first, the phase difference layer converts the incident p-polarized light projection light into circularly polarized light. Then, the selective reflection layer selectively reflects the circularly polarized light and re-incident the phase difference layer. Moreover, the phase difference layer converts the circularly polarized light into p-polarized light. Thus, the projection image display laminated film 10B reflects the incident p-polarized light projection light as p-polarized light.

[0284] Therefore, the phase difference layer is set to convert the incident p-polarized light into circularly polarized light of the rotation direction reflected by the selective reflection layer according to the rotation direction of the circularly polarized light selectively reflected by the selective reflection layer. That is, when the selective reflection layer selectively reflects right-handed circularly polarized light, the phase difference layer is set to make the incident p-polarized light become right-handed circularly polarized light. Conversely, when the selective reflection layer selectively reflects left-handed circularly polarized light, the phase difference layer is set to make the incident p-polarized light become left-handed circularly polarized light.

[0285] In the projection image display system 30, the projector 34 preferably irradiates the projection light of p-polarized light onto the projection image display laminated glass 32. By setting the projection light irradiated by the projector 34 onto the projection image display laminated glass 32 as p-polarized light, the reflection of the projection light caused by the first glass substrate 22 and the second glass substrate 26 of the projection image display laminated glass 32 is greatly reduced, thereby suppressing the observation of undesirable conditions such as double images.

[0286] Preferably, the projector 34 irradiates the windshield with p-polarized light at the Brewster angle, thereby eliminating reflection of the projection light on the first glass substrate 22 and the second glass substrate 26 and displaying a clearer image.

[0287] (Projector)

[0288] A "projector" is a "device that projects light or an image", including a "device that projects a depicted image", and emits projection light that carries an image to be displayed. The projector preferably emits p-polarized projection light.

[0289] The projector only needs to be arranged so that the projection light of p-polarized light carrying the image to be displayed can be incident on the laminated glass for projected image display at an oblique incident angle.

[0290] The projector preferably includes a drawing device and reflects and displays the image (real image) drawn on the small intermediate image screen as a virtual image through a combiner.

[0291] Furthermore, it is preferable that the projector has a variable imaging distance of the virtual image (that is, an imaging position of the virtual image).

[0292] As methods for changing the imaging distance of a virtual image in a projector, for example, there can be cited a method of moving an image generating surface (screen) (refer to Japanese Patent Gazette No. 2017-021302), a method of switching between multiple optical paths with different optical path lengths (refer to WO2015 / 190157), a method of changing the optical path length by inserting and / or moving a reflector, a method of changing the focal length by using a group lens as an imaging lens, a method of moving a projector, a method of switching between multiple projectors with different imaging distances of virtual images, and a method of using a zoom lens (refer to WO2010 / 116912).

[0293] The projector may be a projector in which the imaging distance of the virtual image can be continuously changed, or a projector in which the imaging distance of the virtual image can be switched between two points or three or more points.

[0294] The rendering device may be a device that displays an image itself, or may be a device that emits light capable of rendering an image.

[0295] In the drawing device, the light from the light source can be adjusted by a drawing method such as a light modulator, a laser brightness modulation mechanism, or a light deflection mechanism for drawing. The drawing device refers to a device that includes a light source and, depending on the drawing method, also includes a light modulator, a laser brightness modulation mechanism, or a light deflection mechanism for drawing.

[0296] The light source is not limited, and known light sources used for projectors, drawing devices, displays, and the like, such as LEDs (light emitting diodes), organic light emitting diodes (OLEDs), discharge tubes, and laser light sources, can be used.

[0297] Among them, LEDs and discharge tubes are preferred because they are suitable as light sources for drawing devices that emit linearly polarized light, and LEDs are more preferred.

[0298] The drawing method can be selected according to the light source used, etc., and is not particularly limited.

[0299] Examples of the drawing method include a fluorescent display tube, an LCD (Liquid Crystal Display) method using liquid crystal, an LCOS (Liquid Crystal on Silicon) method, a DLP (registered trademark) (Digital Light Processing) method, and a scanning method using a laser. The drawing method may be a method using a fluorescent display tube that is integrated with a light source. As a drawing method, an LCD method is preferred.

[0300] The light emitted from the drawing device may be linearly polarized light or natural light (non-polarized light).

[0301] The emitted light of a drawing device using an LCD or LCOS drawing method and a drawing device using a laser light source is essentially linearly polarized light. When the emitted light of the drawing device is linearly polarized light and the emitted light includes light of multiple wavelengths (colors), the polarization directions (transmission axis directions) of the multiple wavelengths of light are preferably the same. It is known that the polarization directions of commercially available drawing devices in the wavelength regions of red light, green light, and blue light as emitted light are sometimes not uniform (refer to Japanese Patent Publication No. 2000-221449). Specifically, there is a known example in which the polarization direction of green light is orthogonal to the polarization directions of red light and blue light.

[0302] As described above, the drawing device may be a device using an intermediate image screen. The "intermediate image screen" is a screen that draws an image. That is, in a case where the light emitted from the drawing device is not yet recognizable as an image, the drawing device forms a recognizable image on the intermediate image screen through the light. The image drawn on the intermediate image screen may be projected onto the combiner by transmitting the light of the intermediate image screen, or may be projected onto the combiner by reflecting the light on the intermediate image screen.

[0303] The laminated glass for projected image display is preferably used in combination with a projector using a laser, LED, OLED (organic light emitting diode), or the like whose emission wavelength is discontinuous in the visible light region as a light source.

[0304] The incident light is preferably incident at an oblique incident angle of 45 to 70° relative to the normal line of the projection image display laminated film in the projection image display laminated glass. The Brewster angle of the interface between glass with a refractive index of about 1.51 and air with a refractive index of 1 is about 56°. By making the p-polarized light incident at the above angle range, the incident light for displaying the projection image has less reflected light from the surface of the projection image display laminated glass on the visual recognition side relative to the selective reflection layer, and an image with less influence of ghosting can be displayed.

[0305] The angle is preferably 50 to 65°. In this case, the projection image can be observed at an angle of 45 to 70° (preferably 50 to 65°) relative to the normal of the selective reflection layer on the side opposite to the incident light.

[0306] The incident light may enter the laminated glass for projection image display from any direction such as up, down, left, and right, as long as it is determined in accordance with the visual recognition direction. For example, it is preferably a structure in which the incident light enters from below at the above-mentioned oblique incident angle during use.

[0307] Furthermore, it is preferable that the laminated film for projection image display of the laminated glass for projection image display is arranged so as to reflect incident p-polarized light.

[0308] The present invention is basically constituted as above. The laminated glass for projection image display, the laminated glass for projection image display and the projection image display system of the present invention are described in detail above, but the present invention is not limited to the above-mentioned embodiments, and various improvements or changes can be made within the scope of the gist of the present invention.

[0309] Example

[0310] Below, enumerate embodiment, further the present invention is specifically described.As long as do not depart from the gist of the present invention, then the material, reagent, amount and ratio thereof and operation etc. shown in following examples, comparative example, preparation example can be appropriately changed.Therefore, the scope of the present invention is not limited to following examples.

[0311] <Preparation of the composition for forming a cholesteric liquid crystal layer, the composition for forming a phase difference layer, and the composition for forming a polarization conversion layer>

[0312] The components were mixed in the formulation shown in Table 1 below, and the obtained mixture was filtered through a polypropylene filter with a pore size of 10 μm to prepare cholesteric liquid crystal layer forming compositions BG1, R1, IR1, retardation layer forming composition A1, and polarization conversion layer forming composition TW-1.

[0313] [Table 1]

[0314]

[0315] The unit of the numerical values ​​in the above Table 1 is part by mass.

[0316] The details of each compound described in Table 1 are shown below.

[0317] [Chemical formula 1]

[0318] Mixture 1

[0319]

[0320] Values ​​are mass %

[0321] [Chemical formula 2]

[0322] Orientation control agent 1

[0323]

[0324] [Chemical formula 3]

[0325] Orientation control agent 2

[0326]

[0327] <Saponification of cellulose acylate film>

[0328] A cellulose acylate film having a thickness of 40 μm was produced by the same production method as Example 20 of International Publication No. 2014 / 112575. In addition, UV-531 manufactured by Yancheng Disheng Chemical Co., Ltd. was added to the cellulose acylate film as an ultraviolet absorber. The added amount was set to 3 phr (per hundred resin).

[0329] The prepared cellulose acylate film was passed through a dielectric heating roll at a temperature of 60° C. to raise the surface temperature of the film to 40° C., and then an alkali solution of the following composition was applied at a coating amount of 14 mL / m 2 using a bar coater. 2 The film was coated on one side and heated to 110°C by a steam-type far-infrared heater (Noritake Co.,

[0330] Ltd.) for 10 seconds.

[0331] Next, pure water (3 mL / m) was applied using a bar coater in the same manner. 2 .

[0332] Next, after washing with water using a jet coater and dehydration using an air knife were repeated three times, the film was allowed to stand in a drying zone at 70° C. for 5 seconds for drying, thereby producing a saponified cellulose acylate film 1 .

[0333]

[0334] <Formation of Orientation Layer>

[0335] The saponified surface of the cellulose acylate film 1 (support) obtained after the saponification treatment was coated with 24 mL / m 2 The coating liquid for forming an alignment layer having the composition shown below was dried with warm air at 100° C. for 120 seconds to obtain an alignment layer having a thickness of 0.5 μm.

[0336]

[0337] (Modified polyvinyl alcohol)

[0338] [Chemical formula 4]

[0339]

[0340] <Production of reflective film>

[0341] The oriented layer prepared above was subjected to a rubbing treatment (rayon cloth, pressure: 0.1 kgf (0.98 N), rotation speed: 1000 rpm (revolutions per minute), conveying speed: 10 m / min, number of times: 1 reciprocating time) in a direction rotated 45° clockwise with respect to the long side direction of the support.

[0342] The rubbing alignment layer surface was coated with the phase difference layer forming composition A1 using a wire bar and dried, and then placed on a hot plate at 50°C. In an environment with an oxygen concentration of 1000 ppm or less, the electrodeless lamp "D bulb" (60 mW / cm 2 ) was irradiated with ultraviolet light for 6 seconds to form a phase difference layer.

[0343] The front retardation of the produced retardation layer at a wavelength of 550 nm was measured using AxoScan manufactured by Axometrics and found to be 126 nm.

[0344] On the surface of the phase difference layer prepared above, the cholesteric liquid crystal layer forming composition IR1 was further coated at room temperature using a wire bar until the thickness of the dry film after drying became 0.4 μm. After the coated layer was dried at room temperature for 30 seconds, it was heated at 85°C for 2 minutes. Thereafter, the phase difference layer was subjected to a light source at 60°C using a D bulb (90 mW / cm2) manufactured by FusionUV Systems Inc. in an environment with an oxygen concentration of 1000 ppm or less. 2 A lamp was used) and ultraviolet rays were irradiated for 6 to 12 seconds at an output of 60% to fix the cholesteric liquid crystal phase, thereby obtaining a cholesteric liquid crystal layer IR1 with a thickness of 0.4 μm.

[0345] Next, on the surface of the obtained cholesteric liquid crystal layer IR1, the same steps were repeated using the cholesteric liquid crystal layer-forming composition BG1 to laminate a cholesteric liquid crystal layer BG1 having a thickness of 0.84 μm.

[0346] Next, on the surface of the obtained cholesteric liquid crystal layer BG1, the same steps were repeated using the cholesteric liquid crystal layer-forming composition R1 to laminate a cholesteric liquid crystal layer R1 having a thickness of 0.36 μm.

[0347] Thus, a film having a reflective layer composed of three cholesteric liquid crystal layers was obtained. The transmission spectrum of the film was measured using a spectrophotometer (manufactured by JASCO Corporation, V-670), and a transmission spectrum having selective reflection center wavelengths at wavelengths of 515 nm, 685 nm, and 775 nm was obtained.

[0348] The composition TW1 for forming a polarized light conversion layer was applied to the cholesteric liquid crystal layer R1 prepared above using a wire bar at room temperature until the thickness of the dry film after drying became 0.8 μm. The applied layer was dried at room temperature for 30 seconds and heated at 85°C for 2 minutes. Thereafter, the film was heated at 60°C in an environment with an oxygen concentration of 1000 ppm or less using a D bulb (90 mW / cm 2 The reflective film was obtained by irradiating ultraviolet rays at 60% output for 6 to 12 seconds to fix the polarized light conversion layer.

[0349] <Preparation of heat seal layer forming composition>

[0350] The components were mixed in the formulation shown in Table 2 below, and the obtained mixture was filtered through a polypropylene filter having a pore size of 10 μm to prepare heat seal layer forming compositions HS-1 to HS-8.

[0351] [Table 2]

[0352]

[0353] The unit of the numerical values ​​in the above Table 2 is part by mass.

[0354] AEROSIL RX300 (manufactured by NIPPON AEROSIL CO., LTD., average primary particle size 7 nm) was added to butyl acetate to a solid content concentration of 5 mass %, and stirred for 30 minutes with a magnetic stirrer. Thereafter, ultrasonic dispersion was performed for 10 minutes using an ultrasonic disperser (manufactured by SMT Co., Ltd., Ultrasonic Homogenizer UH-600S) to prepare a silica particle dispersion.

[0355] A portion of the obtained silica particle dispersion was extracted and used for average secondary particle diameter measurement. The average secondary particle diameter of the silica particles in the silica particle dispersion was measured using Microtrac MT3000 (manufactured by Microtrac BEL Corp.) and was found to be 190 nm.

[0356] Furthermore, the above-obtained silica particle dispersion was used to prepare the above-described heat seal layer-forming composition.

[0357] In addition, the content of the silica particles in Table 2 indicates the content of the silica particles themselves.

[0358] <Example 1>

[0359] The heat seal layer 1 was formed by applying the heat seal layer forming composition HS-1 to the surface of the support of the reflective film not coated with the retardation layer using a wire bar until the film thickness after drying was 1 μm, and then drying was performed at 100° C. for 1 minute.

[0360] Next, the heat seal layer 2 was formed by applying the heat seal layer forming composition HS-2 on the surface of the obtained heat seal layer 1 using a wire bar until the film thickness after drying became 5 μm, and then drying was performed at 100° C. for 2 minutes.

[0361] The surface of the heat-sealing layer 2 of the laminated film produced above was sandblasted (time: 3 seconds) to obtain a laminated film 1 for projection image display having a phase difference layer, a 3-layer cholesteric liquid crystal layer (selective reflection layer) and a polarization light conversion layer on one surface of the support body and a heat-sealing layer with a thickness of 6.0 μm on the other surface.

[0362] <Example 2 and Example 3>

[0363] Except that the composition for forming the heat seal layer 2 was changed as shown in Table 3, the same procedure as in Example 1 was carried out to obtain laminated films 2 and 3 for projected image display.

[0364] <Example 4>

[0365] A projection image display laminate film 4 of the embodiment was obtained by the same procedure as in the embodiment 3 except that the sandblasting time was changed to 10 seconds.

[0366] <Example 5>

[0367] A projected image display laminated film 5 of the embodiment was obtained by the same procedure as in the embodiment 3 except that the sandblasting time was changed to 15 seconds.

[0368] <Example 6>

[0369] On the surface of the heat seal layer 2 after sandblasting, the 2 A projection image display laminate film 6 was obtained by the same procedure as in Example 5 except that a corona treatment was further performed at a treatment amount of .

[0370] <Example 7>

[0371] A laminated film 7 for projected image display was obtained by the same procedure as in Example 6 except that the coating was performed until the film thickness of the heat seal layer 2 after drying became 9 μm.

[0372] <Example 8>

[0373] The heat seal layer 1 was formed by applying the heat seal layer forming composition HS-1 to the surface of the support of the reflective film prepared above on which the retardation layer was not applied, using a wire bar until the film thickness after drying became 1 μm, and then drying was performed at 100° C. for 1 minute.

[0374] Next, the heat seal layer 2 was formed by applying the heat seal layer forming composition HS-5 on the surface of the obtained heat seal layer 1 using a wire bar until the film thickness after drying became 9 μm, and then drying was performed at 120° C. for 2 minutes.

[0375] Through the above steps, a projection image display laminate film 8 having a retardation layer, three cholesteric liquid crystal layers (selective reflection layers) and a polarization conversion layer on one surface of a support and a 10.0 μm thick heat seal layer on the other surface of the support was obtained.

[0376] <Examples 9 and 10>

[0377] Except that the composition for forming the heat seal layer 2 was changed as shown in Table 3, the same procedure as in Example 8 was carried out to obtain laminated films 9 and 10 for projected image display.

[0378] <Comparative Example 1>

[0379] A projected image display laminated film C1 was obtained in the same manner as in Example 8 except that the composition for forming the heat seal layer 2 was changed to that shown in Table 3 and coating was performed using a wire bar until the film thickness after drying became 1.5 μm.

[0380] <Comparative Examples 2 and 3>

[0381] Laminated films C2 and C3 for projection image display were obtained in the same procedure as in Comparative Example 1 except that the composition for forming the heat seal layer 2 was changed to that shown in Table 3 and the coating was performed using a wire bar until the film thickness after drying became 5 μm.

[0382] <Measurement>

[0383] (Average value A of arithmetic mean height Sa)

[0384] For three different parts of the surface of the heat-sealing layer of the projection image display laminated film obtained in the embodiments and comparative examples, Vertscan2.0 (manufactured by Ryoka Systems Inc.) was used to measure the arithmetic mean height Sa within the field of view size of 3700μm×4900μm under the conditions of lens magnification ×2.5, barrel magnification ×0.5, and Wave mode, and their average value (arithmetic mean) was taken as the average value A.

[0385] (Average value B of arithmetic mean roughness Sa)

[0386] For three different locations on the surface of the heat-sealing layer of the projection image display laminated film obtained in the embodiments and comparative examples, the arithmetic mean height Sa within the field of view size of 180 μm × 240 μm was measured using Vertscan2.0 (manufactured by Ryoka Systems Inc.) under the conditions of lens magnification × 50, barrel magnification × 0.5, and Wave mode, and their average value (arithmetic mean) was taken as the average value B.

[0387] (Water contact angle)

[0388] For three different locations on the surface of the heat seal layer of the projection image display laminated film obtained in the examples and comparative examples, a contact angle measuring instrument CA-X (manufactured by Kyowa Interface Science Co., Ltd.) was used to make a droplet of 1.0 mm in diameter on the tip of a needle under an environment of 20°C and 65% RH, and the droplet was made in contact with the surface of the heat seal layer. The angle on the pure water side was measured by the angle formed by the tangent line to the pure water surface at the point where the heat seal layer surface contacted the pure water 25 seconds after the heat seal layer surface contacted the pure water, and the average value thereof was taken as the water contact angle of the projection image display laminated film.

[0389] <Manufacturing of laminated glass>

[0390] On a convex curved glass substrate of 260 mm in length and 330 mm in width and 2 mm in thickness, the projection image display laminated film of 220 mm in length and 290 mm in width obtained in the examples and comparative examples was arranged at the center of the glass substrate with the surface on the heat seal layer side as the contact surface. Thus, a laminated body having the first glass substrate, the heat seal layer 2, the heat seal layer 1, the support, the phase difference layer, the selective reflection layer and the polarization conversion layer in this order was formed.

[0391] On the laminate, a PVB film (intermediate film) manufactured by SEKISUI CHEMICAL CO., LTD. with a length of 260 mm × a width of 330 mm and a thickness of 0.76 mm was arranged, and a convex curved glass substrate (second glass substrate) with a length of 260 mm × a width of 330 mm and a thickness of 2 mm was further arranged thereon. After being kept at 115° C. and 10 kPa (0.1 atmosphere) for 1 hour, the degassing evaluation described later was performed, and then the bubbles were removed by heating at 140° C. and 1.3 MPa (13 atmosphere) for 60 minutes in an autoclave (manufactured by KURIHARASEISAKUSHO Co., Ltd.), thereby obtaining a laminated glass.

[0392] <Evaluation>

[0393] (Image visual recognition)

[0394] The concave surface of the laminated glass obtained by using the laminated film for projection image display of the embodiment and the comparative example was irradiated with P polarized light to project an image, and the deformation of the virtual image produced was observed by changing the distance between the evaluator and the laminated glass, and the image visibility was evaluated according to the following criteria. Evaluations of C or above were considered acceptable.

[0395] A: There is no deformation when observed from a distance of 2m.

[0396] B: No deformation when observed from a distance of 1m, and almost no deformation when observed from a distance of 2m.

[0397] C: There is no deformation when observed from a distance of 1m, but there is slight deformation when observed from a distance of 2m.

[0398] D: There is no deformation when observed from a distance of 1 m, but there is deformation when observed from a distance of 2 m.

[0399] E: There is deformation when observed from a distance of 1m.

[0400] (Degassing)

[0401] As described in the above step of "Preparation of Laminated Glass", when preparing laminated glass, after heating at 140°C and 1.3 MPa (13 atmospheres) for 60 minutes, the number of marks formed by bursting bubbles larger than 1 mm in the laminated glass was visually measured and evaluated according to the following criteria. The fewer marks formed by bursting bubbles, the better the degassing.

[0402] A: There are no traces of bubbles larger than 1 mm being squeezed out.

[0403] B: There are traces of 1 to 5 bubbles larger than 1 mm being squeezed out.

[0404] C: There are traces of 5 to 20 bubbles larger than 1 mm being squeezed out.

[0405] D: There are traces of 20 or more bubbles larger than 1 mm being squeezed out.

[0406] (Impact resistance)

[0407] A falling ball test in accordance with JISR 3212 was performed on the laminated glass obtained by using the laminated films for projection image display of the examples and comparative examples.

[0408] Specifically, for laminated glass cooled at -20°C, a steel ball (227 g, 38 mm in diameter) was dropped from a height of 9 m onto the first glass substrate side of the laminated glass, and the amount of glass falling from the second glass substrate was measured. Evaluation was performed according to the following evaluation criteria. Evaluations of C or above were considered acceptable.

[0409] A: The amount of glass dropped is less than 5g

[0410] B: The amount of glass dropped is 5g or more and less than 10g

[0411] C: The amount of glass dropped is 10g or more and less than 15g

[0412] D: The amount of glass dropped is 15g or more

[0413] In Table 3, the column "Corona treatment" indicates whether the surface of the heat seal layer 2 was subjected to corona treatment. "No" indicates that it was not subjected to corona treatment, and "Yes" indicates that it was subjected to corona treatment.

[0414] In Table 3, the column "Sandblasting" indicates whether sandblasting was performed on the surface of the heat seal layer 2. "No" indicates that it was not performed, and "Yes" indicates that it was performed. In addition, "Yes, Weak" indicates that the sandblasting time was 3 seconds, "Yes, Medium" indicates that the sandblasting time was 10 seconds, and "Yes, Strong" indicates that the sandblasting time was 20 seconds.

[0415] The total value of the "layer thickness [μm]" of the "heat seal layer 1" and the "layer thickness [μm]" of the "heat seal layer 2" in Table 3 corresponds to the average thickness of the heat seal layer.

[0416] [Table 3]

[0417]

[0418] As shown in Table 3, it was confirmed that the laminated film for projected image display of the present invention exhibited a predetermined effect.

[0419] Among them, from the comparison of Examples 1 to 3, it was confirmed that the effect was more excellent when the average value A was 30 nm or less (preferably 20 nm or less).

[0420] Furthermore, from the comparison of Examples 3 to 5, it was confirmed that the effect was more excellent when the average value B was 15 nm or more (preferably 20 nm or more).

[0421] Furthermore, from the comparison between Example 5 and Example 6, it was confirmed that the effect was more excellent when the water contact angle of the surface of the heat seal layer on the side opposite to the support side was 90° or less.

[0422] Description of Reference Numerals

[0423] 10A, 10B, 100 - laminated film for projection image display, 12, 102 - support body, 14, 104 - selective reflection layer, 16, 106 - heat sealing layer, 20, 32 - laminated glass for projection image display, 22 - first glass substrate, 24 - intermediate layer, 26 - second glass substrate, 30 - projection image display system, 34 - projector, 108 - glass substrate.

Claims

1. A laminated film for projection image display, comprising: Support body; A selective reflection layer disposed on one surface side of the support: and a heat seal layer disposed on the other surface side of the support, The average thickness of the heat-sealing layer is more than 5 μm. The arithmetic mean height Sa in a field of view of 3700 μm in length and 4900 μm in width is measured at three different positions on the surface of the heat seal layer on the side opposite to the support body side, and the average value A of the arithmetic mean height Sa at each position is 40 nm or less. The arithmetic mean height Sa in a field of view of 180 μm in length and 240 μm in width was measured at three different locations on the surface of the heat seal layer opposite to the support side, and the average value B of the arithmetic mean height Sa at each location was 7 nm or more.

2. The projection image display laminated film according to claim 1, in, The water contact angle of the surface of the heat seal layer on the side opposite to the support side is 90° or less.

3. The projection image display laminated film according to claim 1, in, The heat seal layer includes polyvinyl acetal resin.

4. The projection image display laminated film according to claim 1, in, The heat seal layer comprises silicon dioxide particles, The content of the silicon dioxide particles is 1 mass % or more relative to the total mass of the heat seal layer.

5. The laminated film for projection image display according to claim 4, in, The content of the silicon dioxide particles is 7% by mass or more relative to the total mass of the heat seal layer.

6. A laminated glass for projection image display, comprising: 2 glass substrates; and The laminated film for projection image display according to any one of claims 1 to 5, which is disposed between the two glass substrates. 7 . A projection image display system, comprising the laminated glass for projection image display according to claim 6 and a projector for emitting projection light toward the laminated glass for projection image display.

Citation Information

Patent Citations

  • Polymerizable bifunctional acrylate monomer

    JP1989272551A

  • Reactive liquid crystal compound, polymeric liquid crystal compound, liquid crystal composition and liquid crystal element

    JP1994016616A

  • Liquid crystal display element and its production

    JP1995110469A

  • multilayer optical film

    JP1997506837A

  • Liquid crystal (Meth)Acrylate compound, its composition and optical isomer using the same

    JP1999080081A